Comparative Dynamic Seismic Analyses of RC Minarets Strengthened with FRP and Buttresses - Erdem Türkeli (Doğal Afetler ve Çevre Dergisi)
In recent earthquakes occurred in Turkey, an unexpected number of reinforced concrete (RC) minarets were heavily damaged or collapsed causing loss of lives and economic damages. These structures can be counted as the most common constructed slender structures in Turkey. Therefore, the detailed behavior of these slender structures should be determined in order to strengthen the existing ones and construct safer and stronger RC minarets. In this study, the most common constructed types of RC minarets were analyzed under 17 August 1999 Mw 7.4 Kocaeli Earthquake for the determination of the effectiveness of strengthening techniques namely fiber reinforced polymers (FRP) and buttresses. Also, soil-structure interaction (SSI) is included in the dynamic seismic analyses of the minarets as proposed by Burman et al. (2012). At the end of the analyses performed, it was determined that FRP strengthening is more effective in enhancing the seismic response of RC minarets as the height of the minaret increases when compared with the buttress strengthening. Also, the stress demand locations predicted from the dynamic seismic analyses of the representative minarets were found to be consistent with the damages observed in recent earthquakes.